Ageing, gender and class: differences in experiences and livelihood strategies of ageing populations in Harare, Zimbabwe - Gweru, Benjamin (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.